2011
DOI: 10.1161/circresaha.111.242610
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocardial Stem Cell Injection in Patients With Ischemic Cardiomyopathy

Abstract: Rationale Transcatheter, intramyocardial injections of bone marrow derived cell therapy produces reverse remodeling in large animal models of ischemic cardiomyopathy. Objective We used cardiac magnetic resonance imaging (CMR) in patients with LV dysfunction related to remote myocardial infarction (MI) to test the hypothesis that bone marrow progenitor cell injection cause functional recovery of scarred myocardium and reverse remodeling. Methods and Results Eight patients (age 57.2±13.3) received transendoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
258
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 297 publications
(267 citation statements)
references
References 11 publications
4
258
0
3
Order By: Relevance
“…Intra-myocardial injection of autologous bone marrow derived stem cells has been used in adults with chronic ischemic heart disease (i.e. not infarcted) to achieve functional recovery and reverse ventricular remodeling (Williams et al, 2011). Such reports of success strengthen the concept that endogenous stem cells can provide clinically significant benefits to heart disease patients of all ages.…”
Section: Cpc and Therapy For Chdmentioning
confidence: 99%
“…Intra-myocardial injection of autologous bone marrow derived stem cells has been used in adults with chronic ischemic heart disease (i.e. not infarcted) to achieve functional recovery and reverse ventricular remodeling (Williams et al, 2011). Such reports of success strengthen the concept that endogenous stem cells can provide clinically significant benefits to heart disease patients of all ages.…”
Section: Cpc and Therapy For Chdmentioning
confidence: 99%
“…Williams ve ark. [46] ise 2011 yılın-da kronik iskemik kalp hastalı¤ı (K‹KH) olan sekiz hastaya miyokard içine otolog K‹-MKH vermi, bölgesel olarak kasılabilirli¤inin arttı¤ını ve diyastol/sistol sonu hacimlerin küçüldü¤ünü gözlemlemilerdir. [46] Mathiasen ve ark.…”
Section: Self-renewal (Kendini Yenileyebilme)unclassified
“…[46] ise 2011 yılın-da kronik iskemik kalp hastalı¤ı (K‹KH) olan sekiz hastaya miyokard içine otolog K‹-MKH vermi, bölgesel olarak kasılabilirli¤inin arttı¤ını ve diyastol/sistol sonu hacimlerin küçüldü¤ünü gözlemlemilerdir. [46] Mathiasen ve ark. [47] tarafından 2015 yılında yapılan randomize çift-kör ve plasebo-kontrollü bir çalımada, iskemik kalp yetmezli¤i olan 30 ila 80 ya aralı¤ında bulunan 37 hastaya miyokard içine otolog K‹-MKH, 18 hastaya ise plasebo verilmitir.…”
Section: Self-renewal (Kendini Yenileyebilme)unclassified
“…At the same time, the clinical application of MSCs continues to increase markedly. Recently, numerous studies have revealed a variety of mechanisms including paracrine effects, neoangiogenesis, and biomechanical alterations because of scarring [16][17][18]. Moreover, MSCs have been widely tested for their capacity to mitigate autoimmunity.…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%